1975
DOI: 10.1007/bf00218973
|View full text |Cite
|
Sign up to set email alerts
|

Variations of mitotic activity in the adenohypophysis of male Rats during a 24-Hour cycle

Abstract: The mitotic activity in the adenohypophysis of male rats during a 24 hours' cycle has been studied at the time of the spring equinox. The animals were killed by perfusion of fixative. The mitotic activity seems to be the combination of two elements: a relatively low and nearly constant activity with two peaks of high activity. The first one takes place at 6 o'clock (local time) with an index reaching 4.25; the second one occurs at 11 o'clock (local time) and its index is 2.09. The afternoon activity is weak wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…This conflicting result may be due to the fact that there is a diurnal cycle of mitosis in pituitary cells (Nouet and Kujas, 1975) and that the interval of the metaphase is too short to encounter mitotic division.…”
Section: Discussionmentioning
confidence: 99%
“…This conflicting result may be due to the fact that there is a diurnal cycle of mitosis in pituitary cells (Nouet and Kujas, 1975) and that the interval of the metaphase is too short to encounter mitotic division.…”
Section: Discussionmentioning
confidence: 99%
“…Whether peak activity occurs during the night (Carbajo-Perez et al 1991, Oishi et al 1993 or during the day, or as one peak of mitotic activity (McNicol & Carbajo-Perez 1999) or two (Nouet & Kujas 1975) is unclear. Differences in age, sex and breed of rats aside, the very low prevalence of mitotic figures and the unpredictable effects of stress in different holding facilities is likely to make this issue hard to resolve.…”
Section: Circadian Rhythmicity Of Trophic Activitymentioning
confidence: 99%
“…Hunt and Hunt (1966) found drastic changes in mitotic rates during different phases of the estrous cycle in female rats, and the number in mitotic cells in male rats has been observed to increase and decrease over the course of 24 hours (Nouet and Kujas, 1975). More recently, immunohistochemical staining of 36-kd proliferating cell nuclear antigen (PCNA) (Miyachi et al, 1978;Bravo and Celis, 1980), identified as an auxiliary protein of DNA poly-merase-6 (Bravo et al, 1987;Prelich et al, 1987), has been used for studying cell kinetics.…”
mentioning
confidence: 95%